The single woman's guide to retirement - Cullinane, Jan, frey50
"Essential advice on the retirement challenges facing single womenTwenty-five million strong and growing: that's the number of single women 45+ in the United States. The Single Woman's Guide to Retirement is an essential and targeted resource for planning the next steps in your life. Packed with an inclusive blueprint that covers every aspect of retirement along with quizzes, checklists, and sidebars to help readers assess their choices, The Single Woman's Guide to Retirement is the only retirement book single women need. The author addresses important concerns from the perspective of women, who typically have less savings and live longer than men. From investing to dealing with divorce, dating, caregiving and death, from staying physically, emotionally, and spiritually healthy to handling kids, this book weaves personal anecdotes and suggestions from single women with guidance from attorneys, financial planners and certified public accountants. Covers all the retirement-related issues that affect single women, including finances, taxes, divorce, death of a spouse, second careers, and relocation Recommends the best places to retire, hot careers, meaningful ways to get the most out of your retirement, and strategies for healthy living Asks the three questions that will answer the age-old question--should you retire? By combining technical information with insightful anecdotes, the book is a practical and complete resource for single women looking for a happy, successful retirement. It's the only book that addresses all aspects of retirement for single women, combining professional expertise with the real experiences of many single women"--
Retirement and the single woman -- Deciding what to do with 168 hours a week -- Working in retirement: an oxymoron? -- Fitness in body, mind, and spirit -- Where is your heart? Exploring options for living -- A place to call home: what are your choices? -- Divorce, death, dating, dependency, and deepening connections -- Dollars and sense.
"AARP"--Cover.
Keywords: Single women -- Retirement -- United States; Women -- Retirement -- United States; Retirement -- United States -- Planning; Retirement income -- United States -- Planning; BUSINESS & ECONOMICS -- Personal Finance -- Retirement Planning